Integrated control mamagement system of scientific and technical centre in oil company ROSNEFT; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 5 - Malishenko (Malyshenko) A. M. Alexanedr Maximovich; Chetverikov V. V.; Gordievskikh V. V.; Voronin A. V.; Galaktionov E. A.; Gromakov E. I. (2009, 2009)
В фонде НТБ ТПУ отсутствует